The Social Science Blues - Turkheimer, Eric (The Hastings Center report, 2019)
At the dawn of the new century, Robert Plomin was gloomy. As he recounts in Blueprint: How DNA Makes Us Who We Are, attempts to find the DNA responsible for the heritability of behavior failed. Month after month, journals would report new findings of specific genes for behavioral phenotypes, but they never replicated. One amazing genomic methodology after another was developed in biological genetics and applied to medicine, where it succeeded, and then to human behavior, where it failed. This was the moment of Plomin's despair. He had, with great intellectual courage, staked his reputation on the existence of actionable scientific knowledge of the DNA-based genesis of twin-based heritability. But Blueprint is hardly the product of a gloomy author. Quite the opposite: it is a declaration of victory of nature over nurture, a celebration of the vindication of Plomin as a scientist and of behavior genetics as a field of study. What happened between 2000 and 2019 to brighten Plomin's outlook so radically? Were the genes for schizophrenia and intelligence finally discovered? Are we at last on our way to understanding why, at a biological level, all differences in human behavior are substantially heritable? Alas, no. What happened is that Robert Plomin gave up on the search for individual genes that explain heritability and decided to be satisfied with much less.